Valoración económica del secuestro de CO2, de las especies forestales de la parcela V del arboretum en el CIEFOR-Puerto Almendras, Iquitos, Perú, 2021 - Cabrera Sinarahua, Jhossy Sandra (2022)
The investigation was carried out in plot V of the El Huayo Arboretum of CIEFOR-Puerto Almendras, with the aim of determining the economic value of CO2 sequestration. Plot V was evaluated, which recorded 699 trees grouped into 165 forest species. The total biomass in plot V was 245.69 t. The total carbon stored in the biomass of forest species is 122.85 t. The CO2 sequestration of plot V, of the El Huayo Arboretum accumulates 450.84 t. The total economic value of CO2 sequestration by existing forest species in plot V of the El Huayo Arboretum amounts to €34,408.37. The species Alchornea triplinervia is the one that represents the highest economic value with €5652.22 followed by Dimorphandra macrotachya with €2148.12 and Brosimum utile with €1292.85, these species are the most representative of the study. It is necessary to continue with research on the economic valuation of CO2 sequestration in the different forests of the Loreto region, to compare the results with the present study, to be aware of the differences regarding the subject in research forests and natural forests.